A Genetic and Simulated Annealing Combined Algorithm for Optimization of Wideband Antenna Matching Networks. (23rd April 2012) - Chen, Aixin; Jiang, Tiehua; Chen, Zhizhang; Zhang, Yanjun
Abstract : A genetic and simulated annealing combined algorithm is presented and applied to optimize broadband matching networks for antennas. As a result, advantages of both the genetic algorithm (GA) and simulated annealing (SA) are taken. Effectiveness and efficiency of the presented combined algorithm are demonstrated by optimization of a wideband matching network for a VHF/UHF discone-based antenna. The optimized parameters provide significant improvements of VSWR and transducer power gain for the antenna.